Practice-based collection of quality indicator data for a comprehensive quality assessment programme in Canadian family practices. Issue 6 (27th May 2010) - Price, David; Howard, Michelle; Dolovich, Lisa; Laryea, Stephanie; Hilts, Linda; Barbara, Angela
Abstract : Introduction: Quality improvement in primary care can be facilitated by the ability to measure indicators in practice. This paper reports on the process and impacts of data collection on indicators of a quality assessment tool in seven interprofessional group family practices in Ontario, Canada. Methods: The programme addressed indicators and collected data across multiple domains of practice including clinical quality, physical factors, and patient and staff perceptions. A system audit of the practice, a patient survey, a staff satisfaction survey and chart audits (on hypothyroidism and hyperlipidaemia) were designed to measure selected indicators across the domains. Practices were trained and collected their own data. Practices provided feedback on the process and impacts during a postprogramme workshop and on a survey 1 year later. Results: Four-hundred charts audits were completed for each of hyperlipidaemia and hypothyroidism, 319 patient satisfaction surveys were administered in four practices, and the staff satisfaction survey was completed by 77 staff in six practices. Most practices demonstrated indicators of privacy, access and safety. There was more variability in indicators relating to staff professional development and team involvement in meetings. Patient satisfaction with providers was rated highly, whereas some aspects of practice access were rated lower. Practices approached the challenge of participation by engaging multidisciplinary team members and dividing tasks. Most practices reported continued participation in various quality improvement initiatives 1 year later. Conclusions: Using a set of indicators, structured processes and training, family practices find the process of gathering and reviewing their data useful for quality improvement.